First, we can rewrite this expression as:
#((20 * 5)(x^5y^4))/((15 * 6)(x^2y^6)) = ((100)(x^5y^4))/((90)(x^2y^6)) = (10(x^5y^4))/(9(x^2y^6))#
Now, we can use these two rules for exponents to simplify the #x# and #y# terms:
#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))# and #x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))#
#(10(x^color(red)(5)y^color(red)(4)))/(9(x^color(blue)(2)y^color(blue)(6))) = (10x^(color(red)(5)-color(blue)(2)))/(9y^(color(blue)(6)-color(red)(4))) = (10x^3)/(9y^2)#